pengaruh latihan zig zag run dengan bola terhadap keterampilan dribbling pemain sepak bola pandakian football club kecamatan lubuk basung kabupaten agam - Fajri Fajri; Anton Komaini; Pudia M Indika (JURNAL STAMINA, 2019)
The research problem is the lack of dribbling skills of the Pandakian FC football player in Lubuk Basung Sub-District, Agam District. This study aims to determine the effect of zigzag run training on dribbling skills of Pandakian FC soccer players in Lubuk Basung Sub-District, Agam District. This type of research is quasi-experimental research. The population in this study was the whole players of the Lubuk Basung Pandakian Football Club, Lubuk Basung Distrct, Agam Regency, who were registered and actively participated in the training, which numbered 30 people. The sampling technique is purposive sampling technique, the sample in the study amounted to 15 people in the age group 17 years - 18 years. Data collection was carried out by pre-test and post-test the dribbling skills of Pandakian Football Club soccer players in Lubuk Basung District, Agam District using a Dribbling test. Data analysis and hypothesis testing using comparative analysis techniques using different mean test formula (t test) with a significance level α = 0.05. From the data analysis performed, the results are obtained: There is an effect of zigzag run training on dribbling skills of Pandakian football players FC in Lubuk Basung Sub-District, Agam District, with the acquisition of the "t" test coefficient, namely t = 2.48> t table = 1.761.